Applied surface thermodynamics. - Neumann, A. W. 1933-; David, Robert, 1977-; Zuo, Yi, 1976- (Taylor & Francis, 2011)
Surface thermodynamics forms the foundation of any meaningful study of capillarity and wetting phenomena. The second edition of Applied Surface Thermodynamics offers a comprehensive state-of-the-art treatment of this critical topic. It provides students and researchers with fundamental knowledge and practical guidelines in solving real-world problems related to the measurement and interpretation of interfacial properties. Containing 40 percent new material and reorganized content, this second edition begins by presenting a generalized Gibbs theory of ca.
Keywords: Surfaces (Physics); Thermodynamics.; Surface chemistry.; Surface tension.; Contact angle.; elektronické knihy; electronic books